Effectiveness of Using Telemedicine Technology to Improve Elderly Health - Setiawan (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2024)
Elderly or old age is the end of a person's life span which is characterized by physical and psychological changes. Health problems in the elderly are various health conditions that commonly occur in older people. As a person gets older, they will experience comorbidities, such as metabolic disease, hypertension and diabetes mellitus, or as a complication of another disease they suffer from. In the context of elderly health, telemedicine is very important because it allows wider access to health services, especially for elderly people who live in remote areas or have other geographical obstacles. Several studies say that telemedicine is effective in improving the health of the elderly. The aim of this scoping review is to determine the effectiveness of telemedicine technology on the health quality of the elderly and to understand the mechanism of telemedicine technology in improving the health quality of the elderly. Method: Scoping review with literature search using PubMed, SCOPUS, SAGE Journals, Cambridge Core and E-Journal Springer/Springer Link databases with publication years 2020-2024. The findings showed that 10 selected published articles met the criteria and the results showed that telemedicine was effective in improving the health of the elderly.